Restless leg syndrome in systemic lupus erythematosus: Associations with disease activity, quality of life and depression - Parperis, Konstantinos; Philippou, Sofia; Christophi, Costas A.; Constantinou, Argyris; Bargiotas, Panagiotis; Psarelis, Savvas (My University, 2024)
Objectives: The aim of this study was to determine the prevalence of restless leg syndrome (RLS) among patients with SLE, describe their clinical characteristics, examine its impact on health-related quality of life (HRQoL), and evaluate its association with depression. Methods: A total of 124 SLE patients were recruited, with data on demographics, and clinical features collected. RLS diagnosis was based on the international RLS study group criteria, while depression was assessed by the patient health questionnaire. HRQoL was assessed by a disease-specific validated questionnaire, the LupusQoL, pain intensity was examined through the pain visual analogue scale, and disease activity was evaluated via the patient global assessment. These variables were compared between SLE patients with RLS and without RLS using t-tests or Wilcoxon and the chi-square test of independence for categorical variables. A p-value ≤0.05 was considered statistically significant. Results: Among the SLE patients (mean age 48, 87.1 % women), 32 % had RLS. The SLE patients with RLS were found to have a longer delay in diagnosis (1 vs 0.5 years; p = 0.019) and were less likely to be employed (65 % vs 45 %, p = 0.040) compared to non-RLS patients. In addition, RLS patients were more likely to have coexisting Major Depressive Disorder (MDD) (p = 0.019), higher levels of pain (p = 0.006) and disease activity based on patient global assessment (p = 0.014). Further, most of the domains of LupusQoL were significantly lower in the RLS patients group suggesting a worse HRQoL. Conclusion: RLS was present in one-third of the SLE cohort, significantly impairing HRQoL and correlating with depression, higher pain, and increased disease activity. These findings underscore the importance of early RLS detection and management in SLE patients.
Keywords: Disease activity; Major depressive disorder; Restless leg syndrome; Systemic lupus erythematosus; Quality of life